Legal Certainty Regarding Sharia Banking Dispute Resolution In The Context Of Constitutional Court Decision Number 93/PUU/X/2012 - Sodikin; Edi Suhaedi (PT. Gudang Pustaka Cendekia, 2026)
Disputes resolution in the field of Islamic banking are actually arranged in Article 55, paragraph (1), (2), and (3) of the Law on Islamic Banking. The Problem appear when choice of legal forum (choice of forum) for finish dispute banking agreed for choose one of the legal forums in settlement dispute when the parties No want to finish it through religious courts and their contracts No stated in a way clear the choice of legal forum selected. This is where the need for certainty of law in settling the dispute in question arises, and how the Constitutional Court's decision for certainty of law can be realized in Islamic banking disputes. The research method used is descriptive normative. Research results explain that the Decision of the Constitutional Court Number 93/PUU/X/2012 confirms certainty of law by deleting dualism of authority justice, making the Religious Court as an institution the sole authority to finish Islamic banking through track litigation. Thus, it can be concluded that this decision cancels the explanation of Article 55 paragraph (2) of the Sharia Banking Law, eliminates forum selection to the District Court; however, it still allows non-litigation settlement, such as Sharia arbitration. The settlement process of disputes in Islamic banking, as arranged in Article 55 paragraph (1), (2), and (3) of the Sharia Banking Law, has given duties and authorities to courts in the neighborhood religious courts.